Practice guideline update summary: Pharmacologic treatment for pediatric migraine prevention: Report of the Guideline Development, Dissemination, and Implementation Subcommittee of the American Academy of Neurology and the American Headache Society. Issue 8 (17th September 2019) - Oskoui, Maryam; Pringsheim, Tamara; Billinghurst, Lori; Potrebic, Sonja; Gersz, Elaine M.; Gloss, David; Holler‐Managan, Yolanda; Leininger, Emily; Licking, Nicole; Mack, Kenneth; Powers, Scott W.; Sowell, Michael; et al.
Abstract : Objective: To provide updated evidence‐based recommendations for migraine prevention using pharmacologic treatment with or without cognitive behavioral therapy in the pediatric population. Methods: The authors systematically reviewed literature from January 2003 to August 2017 and developed practice recommendations using the American Academy of Neurology 2011 process, as amended. Results: Fifteen class I‐III studies on migraine prevention in children in adolescents met inclusion criteria. There is insufficient evidence to determine if children and adolescents receiving divalproex, onabotulinumtoxinA, amitriptyline, nimodipine and flunarizine are more or less likely than those receiving placebo to have a reduction in headache frequency. Children with migraine receiving propranolol are possibly more likely than those receiving placebo to have an at least 50% reduction in headache frequency. Children and adolescents receiving topiramate and cinnarizine are probably more likely than those receiving placebo to have a decrease in headache frequency. Children with migraine receiving amitriptyline plus cognitive behavioral therapy are more likely than those receiving amitriptyline plus headache education to have a reduction in headache frequency. Recommendations The majority of randomized controlled trials studying the efficacy of preventive medications for pediatric migraine fail to demonstrate superiority to placebo. Recommendations for the prevention of migraine in children include counseling on lifestyle and behavioral factors that influence headache frequency, and assessment and management of comorbid disorders associated with headache persistence. Clinicians should engage in shared decision making with patients and caregivers regarding the use of preventive treatments for migraine, including discussion of the limitations in the evidence to support pharmacologic treatments.